Penerapan Model Pembelajaran Group Investigation Pada Pembelajaran Tematik Di Kelas II 2022 SD Negeri 07 Kauman Kec. Rao Selatan Kab. Pasaman - Nelyanti Nelyanti (Laboratorium Program Studi Pendidikan Sejarah Universitas PGRI Sumatera Barat, 2022)
Through the use of the Group Investigation learning model in Class II Semester July-December 2022 SD Negeri 07 Kauman, Rao Selatan District, Pasaman Regency, this PTK seeks to boost student motivation for thematic learning. The cycle approach is mostly applied in classroom action research (PTK). Actions are completed in two cycles, each of which consists of the planning, implementing, observing, and reflecting stages. I and II cycles were taught three times each. The semester from July to December 2022 consists of instructional activities, and the percentage formula is utilized for data analysis. The study's conclusions include the following: Between Cycle I and II, the students' interest in thematic learning has increased. Average student motivation in cycle I was 45.83%. cycle II, the typical Student motivation increased from 34.45% to 80.28%. We noticed student motivation in cycles I and II. In every way, student motivation increased significantly. The research's action hypothesis, which was accepted, is that adopting the group investigation learning model in Class II semesters July–December 2022 SD Negeri 07 Kauman, South Rao District, Pasaman Regency, students' learning motivation in thematic learning can be boosted.